The research concept of metropolitan areas demographic development (In the case of European part of Russia metropolitan areas) - N. A. Shchitova; V. S. Belozerov; I. A. Soloviev (Наука. Инновации. Технологии)
Introduction. The subject matter of this study is an analysis of approaches for researching of metropolitan area’s development processes. The special attention is given to the problem of in-metropolitan and cross-metropolitan area’s development. The primary research goal is the original concept development of integrated multiscale study of transformable metropolitan area’s demographic space Materials and methods of the research. The study is based on traditional soviet-designed urban geography approaches for defining the basic terms and delimitation of metropolitan areas: As a first main criteria of area’s demarcation the hour and a half or two hours transport accessibility is used. It is suggested to use selectively the second common criteria - the presence of a big city core The results of the study and their discussion. The concept presents main idea, approaches and principles of spatialtemporal analysis of demographic and migration processes in metropolitan areas based on modern research tools. The authors believe that the proposed methodology allows to systematize disembodied data on Russian metropolitan area’s demographic development and reveals the major trends linked with a special and human resources synergy. It is substantiated the idea that metropolitan areas should be classified based on demographic process’s patterns in city cores, suburban and outlying areas. A multiscale mode of analysis allows to reveal not only the common patterns of demographic development, but also determine local and regional factors which are implicitly making impact on a complex picture. Conclusions. Despite the well-understood metropolitan area’s subject-matter there is no integrated studies in Russian scholarly traditions which are aimed to have an integrated analysis of metropolitan area’s demographic development based on spacial features. It is proposed the view that the demographic development is a leading factor of metropolitan area’s development. The proposed concept has revealed the key methodological aspects of subject studies.